What if School as we know it took on a different structure? Disrupted Educational Structures as Catalysts for Rethinking Opportunities for Preventing School Attendance Problems within a Pedagogical Framework - Walther-Hansen, Wilma; Szulevicz, Thomas (Tidsskrift for Uddannelsesvidenskab // Danish Journal of Education Studies, 2025)
Unexplained and involuntary school attendance problems have become an increasing concern in educational systems over the past decade. The issues often lead to professional interventions based on a clinical oriented within-child-deficit model that overlooks the pedagogical surroundings in which the student is situated, potentially alienating students through existing educational structures. Drawing on qualitative interviews with students and staff from two Danish public schools, this article explores how the pandemic- as an unprecedented disruption of school practices- has provided insights into the connection between school attendance issues and pedagogical practices within learning environments. We hypothesize that these insights can inform future strategies for preventing attendance problems. Based on empirical reflections on changed educational structures, the analysis highlights how the concepts of Pedagogical Tact and Collective Transformative Agency could play a key role in preventing school attendance issues within more resonant learning environments.